2015
DOI: 10.1002/dc.23250
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology of sebaceous carcinoma with analysis of p40 antibody expression

Abstract: p40 can be a valuable marker when evaluating tumors with possible sebaceous differentiation. Although p40 expression in SBCs is not as useful for the differential diagnosis that includes poorly-differentiated squamous cell carcinoma, this study, for the first time in the literature, highlights an important observation that p40 can be utilized as a marker for sebaceous lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…4 the positivity of p40 in 20 previously diagnosed cases of sebaceous carcinoma; however, positivity for p40 does not indicate that a tumor is malignant, as p40 is also expressed in the basal or germinative layer of sebaceous epithelium. 5 We suspect that the adipophilin negative, p40 positive cells in our case represent an immature basaloid or germinative component, consistent with that seen in more typical sebaceous epitheliomas, rather than a malignant component. Our case also showed CK5/6 positivity, which may explain the unique appearance of trabeculae formation, since it is expressed in basaloid cells.…”
Section: Discussionsupporting
confidence: 78%
“…4 the positivity of p40 in 20 previously diagnosed cases of sebaceous carcinoma; however, positivity for p40 does not indicate that a tumor is malignant, as p40 is also expressed in the basal or germinative layer of sebaceous epithelium. 5 We suspect that the adipophilin negative, p40 positive cells in our case represent an immature basaloid or germinative component, consistent with that seen in more typical sebaceous epitheliomas, rather than a malignant component. Our case also showed CK5/6 positivity, which may explain the unique appearance of trabeculae formation, since it is expressed in basaloid cells.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, recent studies have shown P40 immunostaining in benign and malignant neoplasms other than SqCC. A recent study has demonstrated the role of P40 as a marker for sebaceous lineage, noting that this antibody can be utilized for diagnosing sebaceous carcinoma in the setting of poorly differentiated carcinoma [30]. P40 is also expressed in the cuboidal tumor cells of sclerosing hemangioma of the lung, but not in the polygonal tumor cells [31,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The role of SOX10 in sebaceous lesions has not been previously investigated; however, negative staining for DOG1 and positive staining for p63, androgen receptor, adipophilin and p40 in these lesions could help differentiate them from AciCC, which shows the opposite immunoprofile [13,17,18,19]. …”
Section: Discussionmentioning
confidence: 99%